PEMANFAATAN MEDIA SOSIAL DALAM MANAJEMEN PROMOSI SEKOLAH UNTUK MENINGKATKAN KUALITAS DAN KUANTITAS PESERTA DIDIK - Muzdalifah Rohami Harahap; Abdul Fattah Nasution; Dela Fahiran Pandiangan; Muhammad Habibi Rangkuti (Cendekia Madani Nusantara, 2026)
The development of social media has driven significant changes in school promotion management practices in the digital age. Social media is not only used as a means of communication, but also plays a strategic role in building the image of educational institutions and increasing the attractiveness of schools amid competition between educational institutions. This study aims to analyze the use of social media in school promotion management and its role in improving the quality and quantity of students. The research method used is library research by reviewing various relevant sources, including books, scientific journal articles, and previous research results related to educational promotion management and the use of social media. Data collection techniques were carried out through literature searches and critical analysis of concepts, theories, and empirical findings that support the research focus. The results of the study show that the planned, consistent, and sustainable use of social media can increase school visibility, strengthen public trust, and expand the reach of promotion effectively and efficiently. In addition, social media plays a role in conveying academic information, achievements, and the school's strengths, which has an impact on increasing the number of applicants and the quality of students accepted. Therefore, social media needs to be optimally integrated into the planning and policy of school promotion management as part of education management that is adaptive to technological developments.